Original paperStrength of contraction in isolated bladder strips of rats: effect of chemotherapeutic agents mitomycin C and farmorubicin - Michielsen, Dirk P.J.; Amy, Jean-Jacques; Coomans, Danny; Storme, Guy; Wyndaele, Jacques (Archives of Medical Science, 2005)
Objectives: The smooth muscle is an important component of the lower urinary tract, as normal voiding depends on its ability to respond appropriately to stimulation. Impairment of the contractile capacity of the vesical smooth muscle may be reflected in the global voiding function. Repeated intravesical instillations with mitomycin C or farmorubicin have a prolonged effect on bladder volume and compliance. The present study was undertaken to determine whether previous intravesical instillations with mitomycin C and farmorubicin influence the contractile responses of the smooth muscle of the bladder in rats. Material and methods: Forty Wistar rats were divided into four groups. Rats in three of the groups had intravesical instillations of either mitomycin C, farmorubicin, or saline. Rats belonging to the 4 th group had no intravesical instillations, and served as normal controls. The doses of drugs administered were based on those used for therapeutic purposes. After an induction course of three weeks, each bladder was cut in four strips (ventral, Elbadawi line, cranial and dorsal). Thereafter 136 bladder strips underwent electrical field stimulation. Results: Contractile responses did not differ significantly depending on bladder location. The most intense contractile responses, however, were noticed in the dorsal bladder strips, and the weakest responses in the cranial pole strips. Previous intravesical instillations with chemotherapeutic agents did not influence the contractile response of the smooth muscle of the bladder. Conclusion: Repeated intravesical instillations with mitomycin C or farmorubicin have no prolonged effect on the contractile strength of the isolated smooth muscle of the bladder.